Metrics and methods in leanness assessment: A literature review - (:unkn) unknown (Universite de Lorraine, 2015)
Lean production which mainly targets the elimination of waste and increase in customer satisfaction requires steps to be followed for implementation. As the literature suggests, the first step of lean implementation is leanness assessment. The implementation process starts after the existing situation is evaluated with respect to the lean indicators via a proper method. The two important factors in leanness assessment are the lean metrics and the methods that are used. There are various studies using quantitative and qualitative lean metrics and different methods. In this study, numerous papers are reviewed and the lean metrics and methods are identified and analyzed with respect to their frequencies. Moreover, the fields that need further research areas are stated.
Keywords: Lean metrics; Leanness assessment; Performance measurement techniques